Hubungan Kesadaran Individu Dengan Penerapan Patient Safety di Rumah Sakit Umum Daerah S. K. Lerik Kupang - Kori Limbong (JURNAL INFO KESEHATAN, 2018)
Patient safety (patient safety) is one of the dimensions of quality that is currently the center of attention for healthcare practitioners on a national and international scale. This study aims to determine the factors associated with the application of patient safety in the inpatient room of the S.K Regional General Hospital. Lerik Kupang. This study uses a cross-sectional method with a correlation descriptive design. The population is all nurses in the inpatient unit of the S.K General Hospital. The number of 40 people with physical samples is the total population that meets the inclusion criteria of 34 people. The analysis used is the percentage for univariate and chi-square analysis to see the relationship between individual awareness and the application of patient safety by nurses in the inpatient room of the S.K Regional General Hospital. Lerik Kupang. The results showed that 20 respondents (59%) had poor individual awareness and the remaining 13 (38%) had good individual awareness in applying patient safety, 20 (59%) said that the application of patient safety in inpatient rooms was not good and the remaining 13 (38 %) said that the application of patient safety is good. From the results of chi-square analysis shows that there is a significant relationship between individual awareness with the application of patient safety at the S.K Regional General Hospital. Lerik Kota Kupang with a p-value of 0.003.